Telephone hotlines for infectious disease outbreaks in Africa: A review and qualitative study - Noah T. Fongwen; Almighty Nchafack; Kyeng M. Tetuh; Jason J. Ong; Joseph D. Tucker; Gwenda Hughes; Rosanna Peeling (AOSIS, 2024)
Background: Mobile health interventions like telephone hotlines face challenges that may threaten their use, adoption and sustainability in Africa. Aim: We sought to understand the barriers and facilitators for sustainability of telephone hotlines used in infectious disease outbreaks in Africa using a scoping review and a qualitative study. Setting: Participants form 12 African countries and Database searches. Methods: Databases were searched for articles on the barriers and/or facilitators in operating telephone hotlines for outbreaks in Africa. One-on-one interviews and focus group discussions with 30 participants from 12 African countries were also conducted. Emerging themes from the review and interviews were identified and synthesised to focus on barriers and facilitators for the sustainability of the hotlines. Results: The search identified 1153 citations, and 25 studies were finally included. The articles were from 20 African countries. The government was the main source of funding in four countries. Barriers with calls and data management were the most frequent. Human resource barriers such as limited staff, high staff turnover, a lack of incentives and motivation were also significant. Financial barriers were the high cost of operation and huge dependence on external funders. Technological and infrastructural hurdles included limited Internet and phone coverage, malfunction and a lack of interoperability of software. Transitioning to either complete or shared government ownership with diversification and integration of the hotline into routine use was the main facilitator for sustainability. Conclusion: Strengthening technical capacity in telephone hotlines and ensuring financial sustainability are critical. Increased government support is needed. Contribution: More studies on costing will help in developing financial sustainability models for Africa.